2022
DOI: 10.1039/d1ra08066k
|View full text |Cite
|
Sign up to set email alerts
|

Stearic acid modified nano CuMOFs used as a nitric oxide carrier for prolonged nitric oxide release

Abstract: Nitric oxide (NO) shows high potential in the cardiovascular system with anticoagulant and antibacterial efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
(29 reference statements)
2
1
0
Order By: Relevance
“…Compared with the XRD of the pristine fabric, the coated samples showed many characteristic peaks, which were not found in the pristine fabric, indicating that the two coatings had been successfully introduced into the fabric surface. The relative intensities of Cu‐MOFs@SA and CS@Cu‐MOFs@SA coatings were primarily consistent with the classic HKUST‐1, [ 16,17 ] as shown in Figure 2a. Meanwhile, the introduction of chitosan did not appear to change the material's crystal structure.…”
Section: Resultssupporting
confidence: 75%
“…Compared with the XRD of the pristine fabric, the coated samples showed many characteristic peaks, which were not found in the pristine fabric, indicating that the two coatings had been successfully introduced into the fabric surface. The relative intensities of Cu‐MOFs@SA and CS@Cu‐MOFs@SA coatings were primarily consistent with the classic HKUST‐1, [ 16,17 ] as shown in Figure 2a. Meanwhile, the introduction of chitosan did not appear to change the material's crystal structure.…”
Section: Resultssupporting
confidence: 75%
“…Two peaks of 2852 and 2917 cm –1 appear in the FTIR spectra of pure SA and ZnO/Cu–ZnMOFs@SA, which could be assigned to the vibration of the −CH 3 and −CH 2 groups of SA. The results confirmed that SA exists on the ZnO/Cu–ZnMOFs@SA surface, , contributing to its superhydrophobicity.…”
Section: Resultssupporting
confidence: 68%
“…Numerous studies were done to modulate the release of NO. [57][58][59][60] The in vitro release of NO entrapped on the SP NPs was investigated in PBS at pH 7.4 and temperature 37 ± 2 °C to simulate the intestinal environment and the CDR (%) was found to be 97.37 ± 8.19% within 24 h. Fig. 3 demonstrates that SP NPs successfully regulate and lower the release rate of NO.…”
Section: Discussionmentioning
confidence: 95%